Finding Meaning in Contradiction on Employee Review Sites — Effects of Discrepant Online Reviews on Job Application Intentions☆. Issue 1 (August 2018) - Könsgen, Raoul; Schaarschmidt, Mario; Ivens, Stefan; Munzel, Andreas
Sharing experiences with peers through online reviews has amplified the impacts of individual articulations on the reputations of firms across many industries. With employee review sites, current and former employees share their positive and negative experiences with their company, which has become an increasingly important aspect for reputation management and for job seekers' decision-making on where to apply. In the present study, the effects of discrepant reviews (i.e., reviews with a high variance in company evaluations) are examined in the context of employer review sites. In particular, we investigate how review discrepancy, persuasion knowledge activation, and constructive company responses affect job seekers' trust in the company and the resulting application intentions. In our preliminary study, we analyzed a sample of 25, 827 published company reviews on the German employee rating site Kununu.de. The results revealed that high levels of discrepant reviews for the same company exist, thus underlining the need for additional studies. In our main study, a 2 (review discrepancy) × 2 (persuasion knowledge activation) × 2 (company response) between-subject-design experiment was conducted with 311 respondents. We find that high levels of discrepancies lead to increased intentions to avoid submitting applications to the focal company and reduced intentions to pursue employment. This study complements the research concerning online reputation by highlighting the relevance of discrepant reviews for job seekers' application intentions.